2011
DOI: 10.4314/ijbcs.v4i4.63058
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the chemical composition of Dacryodes edulis (G. Don) seeds

Abstract: The Chemical composition and the effect of heat treatment on seeds of Dacryodes edulis (G.Don) were studied. In the proximate analysis, the moisture (42.63-48.05%) and carbohydrate (35.94-38.35%) values were the highest. The values of the tannins (21.80-25.77%), alkaloids (10.40-10.60%) and saponins (5.92-6.72%) were higher than the other phytochemicals measured. Potassium (9.0 ± 0.005-11.00 ± 0.10 mg/100g), calcium (2.23 ± 0.006-5.88 ± 0.005 mg/100g) and phosphorus, (1.09 ±0.05-2.01 ± 0.5 mg/100g) were the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 17 publications
7
13
1
3
Order By: Relevance
“…The levels obtained in this study were lower than those reported by N'Gozi-Olehi (2012) Gozi-Olehi, 2012). It activates ATPase during muscular contraction and it is important for blood coagulation (Ujowundu et al, 2010). It has been reported that potassium regulates the heartbeat, it is an important mineral used for muscular contraction maintaining electrolyte balance in humans and its presence in the flours is very useful (Taylor, 2003;Oulaï et al, 2013).…”
Section: Morphological Characteristics Of Safou (Dacryodes Edulis) Frmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels obtained in this study were lower than those reported by N'Gozi-Olehi (2012) Gozi-Olehi, 2012). It activates ATPase during muscular contraction and it is important for blood coagulation (Ujowundu et al, 2010). It has been reported that potassium regulates the heartbeat, it is an important mineral used for muscular contraction maintaining electrolyte balance in humans and its presence in the flours is very useful (Taylor, 2003;Oulaï et al, 2013).…”
Section: Morphological Characteristics Of Safou (Dacryodes Edulis) Frmentioning
confidence: 99%
“…It has been reported that potassium regulates the heartbeat, it is an important mineral used for muscular contraction maintaining electrolyte balance in humans and its presence in the flours is very useful (Taylor, 2003;Oulaï et al, 2013). It is the principal cation of intracellular fluid and it is involved in protein synthesis (Ujowundu et al, 2010). Sodium is associated with the regulation of acid-base equilibrium, protection against dehydration and maintenance of osmotic pressure in the body.…”
Section: Morphological Characteristics Of Safou (Dacryodes Edulis) Frmentioning
confidence: 99%
“…Also, the increase in cholesterol buttresses a gradual dysfunction of the liver. Furthermore, the finding of Ivens et al [32] indicated that, accumulation of dioxins in the liver could modify the metabolism of cholesterol and hormones. And since these compounds are involved in plasma proteins synthesis, hepatocytes accumulation of dioxins may change the peripheral blood status and influence the biochemical response to an inflammatory reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The non-significant increase in the Se concentrations of groups II to IV, and its significant increase in group V animals could be attributed to destruction of antioxidant enzymes used in radical scavenging which use selenium as a cofactor. Selenium is an important component of antioxidant enzymes, such as glutathione peroxidase (GPx), thioredoxin reductase (TrxR), iodothyronine deiodinases (IDD) and alcohol dehydrogenase (Tapiero et al, 2003;Ujowundu et al, 2010a). Ascorbic acid, iron, selenium, zinc and manganese improve the immune functions as antioxidants (Talwar et al, 1989;Ujowundu et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%